CORRELATION OF ATMOSPHERIC LABILITY INDEX TO VERTICAL WIND SHEAR AT I GUSTI NGURAH RAI AIRPORT - Yasa, I Made Tinggal; Yuliara, I Made; Sumaja, Kadek (Universitas Mataram, 2023)
Wind shear is a condition that is detrimental to aircraft because it can cause the aircraft to experience lift, especially during take-off or landing, where wind shear can occur due to bad and unstable weather, so research on the correlation of the atmospheric lability index to wind shear is very important to prevent a plane crash. This research aims to determine the magnitude of the correlation of the atmospheric lability index to the vertical wind shear that occurs at I Gusti Ngurah Rai Airport, Bali. In this research, the Wind Profiler Radar (WPR) brand scintec LAP-3000 was used to obtain wind shear data in the form of wind direction and wind speed data then radiosonde to obtain atmospheric lability index data in the form of Lifted Index (LI), Total-Totals Index (TT), K-Index (KI), and Convective Available Potential Energy (CAPE) index values for each month in 2019-2020. Wind shear measurement was carried out at an altitude of 100-3000 m and data were taken on the difference in wind direction â‰¥ 60o and the difference in wind speed â‰¥ 10 knots. Meanwhile, measurement of the atmospheric lability index is carried out by a flying air balloon that has been equipped with a transmitter. All LI, TT, KI, and CAPE index value data and the number of wind shear events were analyzed with Pearson Product Moment correlation. The value of the correlation coefficient (r) between the LI, TT, KI, and CAPE indices was obtained for successive wind shear events of -0.786; 0,250; 0.738, and 0.713. These results show that the LI, KI, and CAPE index values can be used as a reference to predict wind shear events because they have a strong correlation, obtaining a correlation value between 0.60 to 0.79 compared to the TT index.